DEGRADASI SENYAWA METANIL YELLOW SECARA FOTOKATALITIK MENGGUNAKAN TiO 2 DAN HNO3 - Azkia Alma Ayesha; Akmal Mukhtar; Pepi Helza Yanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Photocatalysis  with  TiO2 -UV  can be  used  to  reduce the content of  waste  dye in the water. Degradation of metanil yellow solution had  been done by photocatalytic using TiO2 as catalyst and  HNO3 as  an oxidator.  Photocatalytic  method used  radiation of  30 watt  UV light  with λ = 437 nm. Degradation of metanil yellow was  done with  several reaction parameters such as time of radiation reaction, mass of  TiO2 , and addition of HNO3. The result of  this research  showed that  metanil yellow 10 ppm  have  degraded 30,755% after 120 minutes radiation,  wheareas  with similiar consentration by addition 0,008  mass of  TiO2 degraded  54,689% with radiation time  up to 45 minutes.  HNO3 as an  oxidator  in degradation without UV radiation can affect the percentage rate of degradation.